Maxillary ameloblastoma in an elderly patient: Report of a surgical approach - Lucas Machado de Menezes; Eduardo Luis de Souza Cruz; José Thiers Carneiro, Junior; Maria Sueli da Silva Kataoka; Sérgio de Melo Alves Júnior; João de Jesus Viana Pinheiro (Elsevier, 2017)
Ameloblastoma is an odontogenic benign tumor of epithelial origin that is characterized by slow, aggressive growth and invasive features. This disease is predominant in the mandible, and in adults between 30 and 40 years of age. It rarely occurs in the maxilla; there are few reported cases in literature, with relative proportions of 1:8 and 1:14 or even 1:58 diagnosed maxilla/mandible ameloblastoma cases, according to published retrospective studies. The purpose of this study is to present and discuss a case of ameloblastoma in the maxilla of an elderly man from the state of Pará in Brazil, who presented with a lesion in the left maxilla. The clinical and surgical steps were chosen based on a set of criteria that will be discussed in this report. Keywords: Ameloblastoma, Maxilla, Maxillofacial surgery